Stability enhancement of anthocyanins from blackcurrant (Ribes nigrum l.) Pomace through intermolecular copigmentation - Mohamad Azman, Ezzat; Yusof, Nurhayati; Chatzifragkou, Afroditi; Charalampopoulos, Dimitris (Multidisciplinary Digital Publishing Institute, 2022)
Intermolecular copigmentation denotes the interaction between colored anthocyanins and the colorless copigment, which is not bound covalently to the anthocyanin molecule. This is the first study to investigate the effect of intermolecular copigmentation on the stability of individual anthocyanins from dried blackcurrant pomace (DBP) using four pure phenolic acids as copigments (ferulic, caffeic, chlorogenic, and rosmarinic acid). Studies were performed at pH 3.0 and pH 6.0, with a copigment/anthocyanin extract molar ratio of 5:1, during storage at 20 °C. At both pH 3.0 and 6.0, rosmarinic acid showed the strongest hyperchromic and bathochromic effects (p < 0.05) on day 0. However, rosmarinic acid showed low stability during storage. At pH 3.0, chlorogenic acid and control samples were capable of maintaining very high levels of total anthocyanin stability during storage (p < 0.05). On the other hand, ferulic acid and control samples had the longest estimated half-life during storage at pH 6.0. Intermolecular copigmentation successfully increased the half-life, color retention, and antioxidant activity of the anthocyanin solution, with cyanidin-3-O-glucoside (C3G) exhibiting the highest stability at both pH values. Overall, anthocyanins from DBP, in combination with chlorogenic or ferulic acid, showed potential for use in commercial food applications.